The combined association of adherence to Mediterranean diet, muscular and cardiorespiratory fitness on low-grade inflammation in adolescents: a pooled analysis (2019)
Purpose: Low-grade inflammation leads to several metabolic disorders, and adherence to a Mediterranean diet (MedDiet), cardiorespiratory fitness (CRF), and muscular fitness (MF) has been considered important markers of metabolic healthy in youth. We investigated the combined association of adherence to Mediterranean diet, and muscular and cardiorespiratory fitness on high-sensitivity C-reactive protein (hs-CRP) in adolescents. Methods: This is a cross-sectional analysis with 1462 adolescents (625 girls) aged 9–18 years from Colombia and Portugal. MedDiet was assessed by Kidmed questionnaire. Shuttle run test was used to assess CRF. MF was assessed by the standing long-jump and handgrip tests. High-sensitivity assays were used to obtain the hs-CRP level. Results: Logistic regression shows that subjects with a low adherence to MedDiet and LowMF/LowCRF had a similar odds (OR = 2.3; 95% CI 1.2–4.0) as those with an optimal adherence to MedDiet and LowMF/LowCRF (OR = 2.3; 95% CI 1.2–5.0) of expressing high inflammatory profile when compared to those with an optimal adherence to MedDiet and HighMF/HighCRF. In addition, ANCOVA showed that subjects classified as high adherence to MedDiet and HighMF/HighCRF had, on average, the lowest levels of hs-CRP (F(7,1454) = 2.051 p = 0.04). Conclusion: The combination of optimal levels of CRF and MF and adherence to MedDiet is associated with lower hs-CRP. However, high MF and CRF seems to counteract the deleterious effect of having a low adherence to the MedDiet on hs-CRP levels. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.